PREVENTION OF HYPERTENSION RISK FACTORS IN ADOLESCENTS: SELF-EFFICACY AND PREVENTIVE PRACTICES - Elki Putri, Silvia; Sahar, Junaiti; Rachmawati, Utami (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
The double burden of communicable and non-communicable diseases (NCDs) since the beginning of 2020 in Indonesia has put adolescents at risk of developing hypertension. The purpose of this community engagement is to promote the eagerness and ability of adolescents to prevent hypertension from an early age, as we observed the increasing self-efficacy and hypertension prevention practices. The health promotion program was carried out at Darul Ilmi Middle School, Depok combining offline and online activities with as many as seven sessions with the involvement of the school authorities. A total of 68 students were included in this program. The results of this Health Promotion Program were: the release of the School Internal Supervisory Team Certificate for the implementation of health promotion activities to prevent hypertension risk factors; health promotion videos that can be used as media for health promotion activities to prevent hypertension risk factors; hypertension screening amongst the 68 students showed that 5.9% had blood pressure 140/90 mmHg; increasing adolescent self-efficacy of 61.76% and adolescent hypertension prevention practices of 60.29% after the implementation of 7 sessions of health promotion program to prevent hypertension risk factors. School involvement strengthens the implementation of health promotion programs for adolescents.